ANALYSIS OF DEMAND MANAGEMENT AND PRODUCTION CAPACITY OF CV. SINAR TEKNIK IN BATAM CITY - Alcung Tasya; Cynthia Valentini; Jessy; Nadiva Surya Permata (Transpublika Publisher, 2022)
CV. Sinar Teknik is an MSME in the service sector for repairing and reconditioning machines, which engages as a lathe workshop that has been established since 2007. As a result of the pandemic and intense competition between businesses, it is difficult for businesses to develop, so service innovation becomes an important role for business development. The purpose of this research is to help the lathe workshop to identify and analyze and fix the problems faced such as the ability of production capacity and demand patterns in the business. The method used in the research is in the form of interviews and observations to get the right data. In addition, the research is described descriptively. The results of the analysis of CV. Sinar Teknik demand planning and uses consumer-appropriate demand management techniques to grow its business. In addition, CV. Sinar Teknik can utilize technology to facilitate business activities so that they become more effective and efficient.